Effect on customers' perceptions of dining experiences due to the promotion of sustainability practices: A qualitative content analysis of user-generated online restaurant reviews in Auckland, New Zealand - Bhargava, Mihir (Auckland University of Technology, 2021)
Although restaurateurs have been gradually adopting sustainability initiatives in restaurants, there is a knowledge gap in understanding the effect of these practices on customers perceptions of restaurants that promote sustainability. Sustainability practices are mostly visible to customers when they are marketed or promoted. Therefore, it is unclear if sustainability initiatives affect customers' perceptions of a dining experience in a restaurant that promotes its sustainability. This study collected secondary qualitative data by utilising 130 online reviews from TripAdvisor. Content analysis was used to systematically categorise and understand the underlying meaning of the data. The study used a deductive approach and built a conceptual model based on existing literature. The online reviews were categorised into eight criteria of dining experience: 1) atmospheric experience, 2) culinary experience, 3) service experience, 4) people experience, 5) co-creation experience, 6) dietary experience, 7) online experience, and 8) eco-experience. Despite the fact that the restaurants sampled for this study promoted sustainability practises, the study's findings show that the most salient dining experience value attributes for customers are culinary experience, service experience, and atmospheric experience. However, sustainability practices had some influence on customers' perceptions of their dining experience, especially on the seven quality factors of dining experience: food quality, menu variety, food pricing, word of mouth, customer loyalty, healthy food, and special diet options. Based on the limitations of the study, future directions for restaurant practitioners and hospitality researchers are recommended. The study also recommends the validation of the quality factors uncovered in this study related to dining experience.
Keywords: customers' perceptions; sustainability; locally grown organic food; online reviews; dining experience; restaurants promoting sustainability; content analysis; User-generated dining experience reviews; restaurants in Auckland